2017
DOI: 10.1016/j.photonics.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement in a quantum neural network based on quantum dots

Abstract: We studied the quantum correlations between the nodes in a quantum neural network built of an array of quantum dots with dipole-dipole interaction. By means of the quasiadiabatic path integral simulation of the density matrix evolution in a presence of the common phonon bath we have shown the coherence in such system can survive up to the liquid nitrogen temperature of 77K and above. The quantum correlations between quantum dots are studied by means of calculation of the entanglement of formation in a pair of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…One of the challenges in the design of quantum neurons is how to create a nonlinear activation function as quantum operations are required to be unitary and linear. There have been a number of publications that focus on creating quantum neural network [4][5][6][7]. One research has found that none of the proposals for quantum neural networks fully exploits both the advantages of quantum physics and computing in neural networks [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the challenges in the design of quantum neurons is how to create a nonlinear activation function as quantum operations are required to be unitary and linear. There have been a number of publications that focus on creating quantum neural network [4][5][6][7]. One research has found that none of the proposals for quantum neural networks fully exploits both the advantages of quantum physics and computing in neural networks [8].…”
Section: Discussionmentioning
confidence: 99%
“…Since the early days of quantum computing, how to use it in the areas of machine learning to gain the quantum speed up has been a long time endeavor [4][5][6][7]. Neural networks can perform versatile learning tasks like clustering, classification, regression, pattern recognition, and more.…”
Section: Introductionmentioning
confidence: 99%
“…Applying this operator in a state in superposition i |x i , 0 the value of x i will be calculated for all i in a single quantum operation, as described in Equation (9).…”
Section: Quantum Computingmentioning
confidence: 99%
“…Attempts to bring quantum computing power to a greater range of problems are the development of quantum machine-learning algorithms as decision trees [6], evolutionary algorithms [7] and artificial neural networks [8,9,10,11,12,13,14,15,16]. In this paper, we are concerned in the field of quantum weightless neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum dots (QDs) have shown an important role in solar photovoltaic (PV), photocatalysts, photosensors and other optoelectronic components due to its quantum confinement effect, small particle size, large specific surface area and high catalytic activity . QDs can capture and transfer photogenerated electrons, accelerating the separation efficiency of photo‐induced carriers.…”
Section: Introductionmentioning
confidence: 99%